(untitled) (Research, Society and Development, 2022)
The objective of this study was to analyze patient safety and Nursing practices in ensuring qualified health care. This is a literature review of the bibliographic type with a qualitative approach. The review arose from the concern “What are the Nursing practices to guarantee qualified and safe patient care?”. For this purpose, a search for studies was carried out in the Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS) and Cumulative Index to Nursing and Allied Health Literature (CINAHL) databases, in the Google Scholar electronic search engine and in the virtual library Scientific Electronic Library Online (SciELO), no use of time clipping. The Nursing has sought to implement incentives and strategies, such as the use of protocols, scales and checklists, so that actions are carried out that enable harm-free, safer and more qualified care. Both managerial and care nursing need to dedicate themselves to establishing actions that aim at safety through information and knowledge. It was possible to perceive that Nursing has contributions of great relevance in relation to patient safety in health care. It is noteworthy that the provision of care in a safe way is still a constant challenge, which requires substantial efforts in order to achieve qualified assistance. It is important to reinforce that the patient safety culture must be a practice implemented by the entire health team and not just by the Nursing team.